Traditional Chinese Medicine in Java - Risty Fahira Nurhalisa; Nindita Swasti Lituhayu; Rudiansyah Rudiansyah (Universitas Negeri Surabaya, 2024)
Before Western health science came to Indonesia, people had long used indigenous or traditional medicine. Traditional Chinese medicine is also one of the conventional medicines in Indonesia, which is a legacy of treatment from other countries and is developing very rapidly, so in its development; traditional medicine is popular in Indonesia, including in the cities of Java. This research aims to see how traditional Chinese medicine has developed in Java. This paper was written using methods and rules in historical science. The first stage is